Thermodynamic Study of Propane Dehydrogenation Into Propylene - Qurratuaini, Hassanusi (2013)
Propane dehydrogenation is a one of a promising route for producing propylene by using thermodynamic analysis to replace traditional cracking methods. The purpose of this study is to product distribution as a function over temperature, to identifying the region of the carbon deposition and to analysis the effect of temperature on the equilibrium constant. Hydrogen production varies significantly according to the operating conditions such as pressure, temperature and feed reactants ratio. The thermodynamic analysis provides important knowledge about the effects of those variables on the process of propane dehydrogenation. The present work was aimed at analyzing the thermodynamic propane dehydrogenation of propylene, using Gibbs free energy minimization with actual temperature and pressure data found in the literature. The results showed that the extent of side reactions strongly depends on the operating conditions. By computing carbon activities in experimental systems, it was also possible to explain deviations between thermodynamic analysis and experimental results regarding carbon deposition. From the results obtained¸ all of possible reactions are endothermic reaction and the dehydrogenation temperature needs to be evaluated to beyond 500 K to 600 K.